2017
DOI: 10.1160/th17-05-0342
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin after an Episode of Haemorrhagic Stroke Is Associated with Improved Survival

Abstract: We aimed at investigating how antiplatelet drug use affected mortality in patients with a history of haemorrhagic stroke (HS). Thus, starting 30 days after an HS episode, we followed 1,004 patients with intracerebral haemorrhage (ICH) and 929 patients with subarachnoid haemorrhage (SAH) for a median of 6.4 years. We estimated the effect of time-dependent exposure to antiplatelets after HS on all-cause mortality. Cox proportional hazard models were used to compute adjusted hazard ratios (aHRs) and 95% confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Therefore, starting antiplatelet therapy seems to be safe and might be beneficial in patients who survived a median of 76 days after intracerebral haemorrhage, most of whom had good functional ability at baseline and a higher probability of good functional outcome at 6-month follow up (table 1, appendix). 19 Our findings, alongside published observational studies,9, 10, 11, 12, 13, 14 provide reassurance about the use of long-term antiplatelet therapy in a range of patients after intracerebral haemorrhage associated with antithrombotic therapy.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, starting antiplatelet therapy seems to be safe and might be beneficial in patients who survived a median of 76 days after intracerebral haemorrhage, most of whom had good functional ability at baseline and a higher probability of good functional outcome at 6-month follow up (table 1, appendix). 19 Our findings, alongside published observational studies,9, 10, 11, 12, 13, 14 provide reassurance about the use of long-term antiplatelet therapy in a range of patients after intracerebral haemorrhage associated with antithrombotic therapy.…”
Section: Discussionsupporting
confidence: 64%
“…In the longer term (months to years), findings from a systematic review and meta-analysis 9 of observational studies of patients with any type of intracranial haemorrhage (ie, intracerebral, subarachnoid, or subdural haemorrhage) showed lower risks of occlusive vascular events and no difference in haemorrhagic events associated with resumption compared with avoidance of antiplatelet therapy. Small, non-randomised observational studies of patients with intracerebral haemorrhage have reported similar associations with starting antiplatelet therapy compared with its avoidance 10, 11, 12, 13, 14. Because of the paucity of evidence, no guidelines with strong recommendations about long-term antiplatelet therapy after intracerebral haemorrhage are available,15, 16 so variations in clinical practice occur 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients who survive ICH may have risk factors for future thromboembolic events, but the role of antithrombotic medications remains a therapeutic dilemma with conflicting evidence and contradictory recommendations [ 36 41 ]. There is currently a lack of solid evidence to guide decisions on whether and when to start or restart treatment in ICH survivors, and both well designed randomized trials and observational studies should be encouraged [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of observational studies of all sub-types of intracranial haemorrhage found lower risks of ischaemic events and no difference in haemorrhagic events associated with antiplatelet drug resumption [9]. Small, non-randomised observational studies restricted to patients with stroke due to ICH have reported similar associations [1014], but these associations were not ‘dramatic’ so randomised controlled trials (RCTs) are needed to resolve this therapeutic dilemma [15]. However, such RCTs have not been published [16].…”
Section: Introductionmentioning
confidence: 99%